ROMR: A ROS-based open-source mobile robot - Linus Nwankwo; Clemens Fritze; Konrad Bartsch; Elmar Rueckert (HardwareX, 2023)
Currently, commercially available intelligent transport robots that are capable of carrying up to 90 kg of load can cost $5,000 or even more. This makes real-world experimentation prohibitively expensive and limits the applicability of such systems to everyday home or industrial tasks. Aside from their high cost, the majority of commercially available platforms are either closed-source, platform-specific or use difficult-to-customize hardware and firmware. In this work, we present a low-cost, open-source and modular alternative, referred to herein as “ROS-based Open-source Mobile Robot (ROMR)”. ROMR utilizes off-the-shelf (OTS) components, additive manufacturing technologies, aluminium profiles, and a consumer hoverboard with high-torque brushless direct current (BLDC) motors. ROMR is fully compatible with the robot operating system (ROS), has a maximum payload of 90 kg, and costs less than $1500. Furthermore, ROMR offers a simple yet robust framework for contextualizing simultaneous localization and mapping (SLAM) algorithms, an essential prerequisite for autonomous robot navigation. The robustness and performance of the ROMR were validated through real-world and simulation experiments. All the design, construction and software files are freely available online under the GNU GPL v3 license at https://doi.org/10.17605/OSF.IO/K83X7. A descriptive video of ROMR can be found at https://osf.io/ku8ag.